A cystic fibrosis patient homozygous for the nonsense mutation R553X. Issue 10 (October 1991) - Bal, J; Stuhrmann, M; Schloesser, M; Schmidtke, J; Reiss, J
Abstract : A cystic fibrosis patient homozygous for the nonsense mutation R553X was identified by mutation screening and the genotype confirmed by DNA sequencing. This patient, the only one described to date who is homozygous for this stop codon in exon 11 of the CFTR gene, is moderately severely affected. Clinical and molecular findings are presented.